Perancangan Instrumen Evaluasi Pembelajaran Berbasis Website di Sekolah Dasar Negeri 55 Air Pacah Kota Padang - Maifit Hendriani; Meria Ultra Gusteti (Universitas Pendidikan Indonesia Kampus Serang, 2021)
The results of observations and interviews conducted at State Elementary School of 55 Air Pacah, during online learning during the covid 19 pandemic there are 2 methods used in learning evaluation. They are (1) using conventional paper-based media that students take home and (2) sending photos of assignments or photos of questions through the WhatsApp application to parents. The use of this method makes it difficult for educators to process values. The use of website-based media in the evaluation of learning is the right solution in the current era. With a website-based evaluation instrument, correction of calculations can be made directly and students immediately get feedback. The training methods are in the form of presentations, demonstrations, hands-on practice with assistance in making evaluation instruments, and assignment methods. As a result of this service activity, educators can understand how to make website-based learning evaluation instruments and be skilled at using them. In addition, since the training was held until now, educators have applied it in online learning.